Implementasi dan Peran Corporate Social Responsibility (CSR) terhadap Kepercayaan Anggota KSPPS BMT NU Balen Cabang Sugihwaras Bojonegoro - Ahmat Arif Syaifudin; Dela Rista Silvia (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
This study discusses the implementation of corporate social responsibility and its role in the trust of members of the sugihwaras KSPPS BMT NU Balen Branch. The purpose of this research is to evaluate the implementation of corporate social responsibility (CSR) and the role of members’ trust in KSPPS  BMT NU Balen Sugihwaras Branch. The research method used is descriptive qualitative with data collection techniques through in-depth interviews and field observation. The results of the study show that KSPPS BMT NU Balen  Sugihwaras Branch has succeeded in implementing a CSR program that is in line with the triple bottom line principle. The CSR program has a positive impact on trust members because they feel that KSPPS BMT NU Balen Sugihwaras Branch is not only profit oriented. But also care about social environment and members feel involved and have the opportunity to participate in CSR programs managed by the company thereby increasing trust and commitment and strengthening the company’s relationship with the community